Peran Guru dalam Pengembangan Materi Kurikulum Pendidikan Agama Islam bagi Siswa Penyandang Tunarungu - Polem, Muhammad; Ningsih, Nur Wahyu; Wulandari, Reksahati; Nursobah, Asep; Karman, Karman; Safari, Edi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the role of teachers in developing Islamic Religious Education curriculum materials for deaf students. The research method uses a qualitative approach with a literature study method. The data source is secondary data, data collection techniques include collecting, editing, categorizing and concluding data, while data analysis by analyzing the content in depth. The results revealed that PAI teachers have as implementer adapters, developers, and researchers in the process of developing Islamic Religious Education curriculum materials for deaf students. Therefore, PAI teachers are required to be creative and innovate to modify learning materials in such a way according to the characteristics and needs of the deaf students taught. Thus, teachers have a very important role in the development of PAI curriculum materials for deaf students. Because the success or failure of the implementation of the curriculum is determined by the teacher himself, because the teacher becomes the spearhead in the implementation of the curriculum.